Variations in Socioeconomic Characteristics, Farming Assests and Livelihood Systems of Leyte Rural Households - Emtage, Nick F.; Suh, Jungho (Annals of Tropical Research, 2005)
This paper presents data from a survey of rural households in four rural communities in Leyte Province, the Philippines. Households in extreme poverty were found in each of the communities; on average more than half the households have cash incomes below the poverty threshold. The situation is particularly severe in one community, where cash incomes are less than half the poverty threshold, land ownership is highly concentrated, few households can supply the majority of their own food, and education levels and housing quality are low. The other three communities all face challenges to their development, but their situation appears to be relatively stable in comparison, possibly due to the outcomes of agricultural infrastructure development and access to land provided through community forestry programs.